The Occurrence of Angle Classes in Patients with Eruption Disturbances of the Maxillary Permanent Canines - P. Černochová; L. Izakovičová-Hollá (Czech Dental Chamber, 2011)
Aim: The aim of the retrospective study was to analyze the relationship between the dental arches expressed by Angle classes in patients with eruption disturbances of the maxillary permanent canines. Material and methods: This retrospective study comprised 871 consecutive Caucasian orthodontic patients who were referred to the Orthodontic Department of Clinic of Stomatology of St. Anne's University Hospital in Brno, Czech Republic, from January 2000 to April 2010. In all the patients included in this study, complete pre-treatment diagnostic data were available. The control group consisted of 603 subjects (376 females and 227 males, mean age 16.9 and 13.9 years, respectively) with physiologically erupted permanent maxillary canines. The palatally displaced canines group included 226 patients: 146 females and 80 males (mean age 18.9 and 19 years, respectively). The buccally displaced canines group comprised 42 patients: 18 females and 24 males (mean age 13.6 and 14.2, respectively). The male-to-female ratio both in the control group and in the group of patients with ectopically erupting canines was 1 : 1.6. The significance of differences in frequencies of Angle classes between the sets was assessed by χ2 square test or Fisher exact test. Results: Palatally displaced canines were found in 25.9 % and buccally displaced canines in 4.9 % of all orthodontic patients. In the set of 871 orthodontic patients included into the retrospective study, Angle Class I occurred in 45.4 %, Angle Class II in 51.5 % (Class II division 1 in 13.3 %, Class II division 2 in 27.2 % and class II without division in 11 %) and Angle Class III in 3.1 %. No major gender-based differences were found in the occurrence of Angle Classes. On the other hand, statistically significant differences in frequencies of Angle Classes between the control set of patients with physiologically erupted canines and the set of patients with palatally displaced canines (P=0.00001) and between the sets with palatally and buccally displaced canines (P=0.015) were found. In the sets of patients with ectopically erupting canines, significantly higher occurrence of Angle Class II division 2 was not determined, but statistically significantly higher occurrence of Angle Class I was found (P=0.000001). Conclusion: Retrusion of the maxillary incisors can be considered a more important factor relating to palatally displaced canines than a type of the Angle Class. In patients with mixed dentition, especially in Angle Class I, regular preventive control of the path of eruption of the maxillary canines is highly recommended.